Theatrically: From Oral Traditions to Televised 'Realities' - Fiebach, Joachim (Substance: A Review of Theory & Literary Criticism, 2002)
Illustrates the functions of theater in different periods of history. Insight on the specificity of the theater; Discussion on the development of a concept in theatricality; Conclusions.